2002
DOI: 10.1002/1521-3773(20020517)41:10<1718::aid-anie1718>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

cis-2-Aminocyclopentanecarboxylic Acid Oligomers Adopt a Sheetlike Structure: Switch from Helix to Nonpolar Strand

Abstract: Rational control over helix and strand secondary structures is possible when conformationally restricted cyclic β‐amino acid residues are incorporated in the β‐peptides. Inversion of the relative configuration of these residues enables the preferred periodic structure to be switched from a helix to a single nonpolar strand (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
102
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 24 publications
(9 reference statements)
9
102
0
3
Order By: Relevance
“…The asymmetric synthesis of polyfunctionalised cyclopentane derivatives has been widely pursued in organic synthesis, with much recent interest focusing around strategies for the asymmetric synthesis of cis-pentacin (1) and trans-pentacin (2), respectively. The cis-diastereoisomer shows potent antifungal activity while Fülop et al have recently demonstrated that oligomers of cis-pentacin adopt a sheet type structure in DMSO [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The asymmetric synthesis of polyfunctionalised cyclopentane derivatives has been widely pursued in organic synthesis, with much recent interest focusing around strategies for the asymmetric synthesis of cis-pentacin (1) and trans-pentacin (2), respectively. The cis-diastereoisomer shows potent antifungal activity while Fülop et al have recently demonstrated that oligomers of cis-pentacin adopt a sheet type structure in DMSO [1].…”
Section: Introductionmentioning
confidence: 99%
“…The cis-diastereoisomer shows potent antifungal activity while Fülop et al have recently demonstrated that oligomers of cis-pentacin adopt a sheet type structure in DMSO [1]. Furthermore, Gellman et al have demonstrated that short chain β-peptides derived from trans-pentacin adopt 12-membered helical structures [2][3][4][5] and when a pyrrolidine-base β-amino acid is incorporated into the hexa-β-peptide 3, it confers water solubility when the ring nitrogen is protonated [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Conformational studies of β-amino acid oligomers are also currently at the focus of interest. [21][22][23][24] Besides their diverse chemical compositions, β-amino acids and their derivatives possess noteworthy pharmacological effects; for example, (1R,2S)-2-aminocyclopentanecarboxylic acid (cispentacin) and some other alicyclic β-amino acids have marked antifungal activity. 25 The present work describes a mild and efficient ring opening of monoterpene-fused β-lactam enantiomers derived from (+)-and (-)-α-pinene, to produce a novel chiral β-amino acid and its derivatives.…”
Section: -8mentioning
confidence: 99%
“…6 cis-2-aminocyclopentanecarboxylic acid oligomers were later shown to be unnatural foldamers more suitable for rational design of new peptides showing novel tertiary structures, because they can adopt sheet like structures by switching from helix to nonpolar strands. 7 Several methods have been described for the synthesis of cyclopentane b-amino acids. 1c However, very few syntheses of polyhydroxylated derivatives have been reported.…”
Section: Introductionmentioning
confidence: 99%